2017
DOI: 10.1002/jlb.2mr0717-310r
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the regulation of APOBEC3 expression: Current evidence and much to learn

Abstract: The apolipoprotein B mRNA editing enzyme catalytic polypeptide-like 3 (APOBEC3) family of cytosine deaminases plays crucial roles in innate immunity through the ability of restricting viral replication by deamination and mutation of viral genomes. The antiviral function of these proteins was first discovered when research in the field of HIV infection revealed that one member of the family, namely APOBEC3G, restricts HIV infection in T lymphocytes and that the viral infectivity factor protein drives the proteo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 81 publications
(250 reference statements)
0
21
0
Order By: Relevance
“…IFNs are main inducers of APOBEC3 expression (55). Our previous work suggested that CCL2 neutralization-mediated increase of APOBEC3A expression in MDMs was type I IFN independent (20,56).…”
Section: Discussionmentioning
confidence: 95%
“…IFNs are main inducers of APOBEC3 expression (55). Our previous work suggested that CCL2 neutralization-mediated increase of APOBEC3A expression in MDMs was type I IFN independent (20,56).…”
Section: Discussionmentioning
confidence: 95%
“…[33][34][35][36] Distinct pathways of transcriptional regulation have been characterized to date for A3A, A3B, and A3G. 37 Virus-cell interactions are characterized for the cancer-associated human papillomavirus (HPV) and polyomavirus that can inactivate specific components of the E2F transcription factor network to de-repress A3B transcription. 38,39 HPV-16 E6 protein also upregulates A3B transcription.…”
Section: Introductionmentioning
confidence: 99%
“…The strongest inducers of APOBEC3 expression are interferons (IFN) (Covino et al, 2018). In the current study, the levels of IFNα and IFNγ in cell supernatant may have been insufficient to induce APOBEC3 expression.…”
Section: Discussionmentioning
confidence: 99%